“Non-Resident Me”: John Bartlet and the Canadian Historical Profession - Aggarwala, Rohit (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1999)
AbstractJohn Bartlet Brebner (1895-1957) was a significant Canadian historian, but his work has been marginalised and discredited in the historiography. A Maritime historian, he continued to study Nova Scotia after leaving the University of Toronto for Columbia University, and this and his work on early explorers and British history led to his espousal of a continental approach that emphasised Canadian-American exchange and a shared British legal and political heritage. A deep liberal, he felt under suspicion because he did not promote either of the two nationalist schools of Canadian history and because he lived in the United States; this feeling moved him to naturalise as an American in 1941 and give up Canadian history. He later regretted this action, as his experiences as a liberal American in the post-war era gave him concerns about the liberal quality of American nationalism. After Brebner's death, his reputation was tarnished by the posthumous publication of an obsolete manuscript and the concerted attack of nationalist historians who, led by Donald G. Creighton, sought to deny legitimacy to even the most nuanced use of the "continental approach."